Training and Preparation of Scientific Papers for the Indonesian Student Research Olympiad in MAN 1 Palu City - Pathuddin, Pathuddin; HB, Usman; Hamid, Abd.; Mainarni, Welli (AMK : Abdi Masyarakat UIKA, 2023)
One of the high schools that is close to campus is MAN 1 Palu City. One of the extracurricular activities in MAN 1 Palu City is KIR (Youth Scientific Work). The interest of students to participate in these activities is very high but requires more intensive coaching. So far, no scientific paper writing training has been conducted for students. This is one of the reasons why students are less able to compete with other schools in Palu in scientific writing competitions. The problems of partners (MAN 1 Palu city) are: a) The KIR group's mastery of writing scientific papers in preparation for the OPSI competition is still low, b) The KIR MAN 1 group in Palu city still often misunderstands the content of scientific papers and scientific paper writing techniques. 3) The lack of resource persons who can be occupied asks if the KIR MAN 1 group in Palu has difficulty in making papers. For this reason, we have held a service activity at MAN 1 Palu City, including) training activities and workshops. Providing training (material for writing scientific papers and techniques for writing scientific papers), at that stage the service team acts as a teacher in presenting materials and examples of scientific works that pass the Indonesian Student Research Olympiad (OPSI). b) Assisting in writing scientific papers.